Length-weight relationships of five fish species from lakes of the Central Amazonian floodplains - Matos, Octavio Ferreira de; Pereira, Diego Valente; Aguiar-Santos, Jamerson; Sampaio, André da Silva; Carvalho, Carlos Edwar Freitas de; Siqueira-Souza, F. K. (Journal of Applied Ichthyology, 2019)
Parameters of the length-weight relationship (LWR) were calculated for five fish species from Amazon Basin. Samplings were carried out in ten lakes of the Solimões River floodplains during the four seasons of the hydrological cycle: rising water, high water, receding water, and low water, during two periods. The first period of eight years included samplings performed from 2001 to 2008 and the second sampling period of two years was from 2012 to 2013. Specimens were captured using gillnets (mesh sizes ranging from 30 to 120 mm between opposite knots) and standardized dimension of 20 m in length × 2 m in height. This study provides the LWR parameters for Acarichthys heckelii, Leporinus trifasciatus, Brycon amazonicus, Curimatella meyeri and Osteoglossum bicirrhosum. © 2019 Blackwell Verlag GmbH